“Gastronomía ancestral y su influencia en el turismo cultural de la ciudad de Riobamba” - Badillo Paredes, Evelyn Fernanda (2020)
The research was carried out in Riobamba city, Chimborazo province. It was developed based on ancient gastronomy and its influence on cultural tourism of the city. The research is a mixed, descriptive type. The design is non-experimental with a documentary and field method. For obtaining data, it was determined that it has a cross section and through the application of surveys; they were previously validated by experts and subsequently became a subject of a reliability test. The results allowed determining the level of knowledge of the traditional food and beverages managers from different venues regarding ancestral gastronomy. It included tourists’ perceptions towards cultural tourism and its relationship with the local gastronomy. The processed data was carried out by using SPSS version 25 software. It generated tables and graphs for being interpreted. Later on, the posed hypothesis was accepted which means that ancestral gastronomy influences significantly on cultural tourism of the city. Based on the results, the proposal consists on the elaboration of a Handbook of ancestral culinary processes in order to rescue and disseminate the ancestral gastronomy of the city. Also, it represents a tool to promote awareness in the community about its culinary heritage.